2020
DOI: 10.1364/oe.398531
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear beam self-imaging and self-focusing dynamics in a GRIN multimode optical fiber: theory and experiments

Abstract: Beam self-imaging in nonlinear graded-index multimode optical fibers is of interest for many applications, such as implementing a fast saturable absorber mechanism in fiber lasers via multimode interference. We obtain a new exact solution for the nonlinear evolution of first and second order moments of a laser beam of arbitrary transverse shape carried by a graded-index multimode fiber. We have experimentally directly visualized the longitudinal evolution of beam self-imaging by means of femtosecond laser puls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 30 publications
8
45
0
Order By: Relevance
“…In contrast, we only experimentally observed fiber damage for input energies above 550 nJ. The discrepancy between simulated and experimental threshold for catastrophic self-focusing can be ascribed to excess multiphoton absorption [7], and to energy side-scattering processes [8], both leading to significant additional losses, which saturate the beam intensity and prevent is collapse. Such mechanisms are not yet incorporated in our model, which only includes TPA.…”
Section: Numerical Simulationsmentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, we only experimentally observed fiber damage for input energies above 550 nJ. The discrepancy between simulated and experimental threshold for catastrophic self-focusing can be ascribed to excess multiphoton absorption [7], and to energy side-scattering processes [8], both leading to significant additional losses, which saturate the beam intensity and prevent is collapse. Such mechanisms are not yet incorporated in our model, which only includes TPA.…”
Section: Numerical Simulationsmentioning
confidence: 59%
“…In particular, the presence of a nonlinear loss mechanism, leading to output energy clamping and SSFS suppression. Such losses are due to multiphoton absorption by the defects of the Germanium doped fiber [7], leading to blue luminescence that is side-scattered from the fiber, at points where the self-imaging shrinks the beam waist [8]. Nonlinear losses quench up to 80% of the transmission, already from the first few centimetres of fiber.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that these solitons have different amplitudes and wavelengths, but nearly equal time duration. Moreover, we experimentally visualized the evolution of spatial self-imaging (SSI) using ultrashort laser pulses, leading to the side-light scattering of photoluminescence and harmonic waves, confirming, indirectly, the invariance of the SSI period [4]. Finally, the evolution of spatiotemporal solitons was also experimentally investigated over relatively long (i.e., up to 1 km) spans of GRIN fiber, demonstrating that the fundamental mode behaves as an attractor with respect to higher-order modes.…”
Section: Introductionmentioning
confidence: 63%
“…In this section, we present a derivation of the exact solution for the nonlinear evolution of first and second-order moments of a laser beam of arbitrary transverse shape in a GRIN fiber [4]. By using operator methods of quantum mechanics, we theoretically determine, in full generality, that the SSI period only varies with the fiber characteristics and the laser wavelength (but it is independent of the laser power); our method also allows for estimating the power threshold for catastrophic self-focusing in a GRIN MMF for a beam of arbitrary incidence.…”
Section: Beam Self-imaging Of Ultrashort Pulsesmentioning
confidence: 99%
“…1 Among MMFs, graded-index (GRIN) fibers exhibit a self-imaging effect, leading to a periodic refractive index modulation induced by the Kerr nonlinearity. 2 Moreover, GRIN fibers have relatively low modal dispersion, which permits long interaction lengths between different fiber modes. Multimode optical solitons, 3 geometrical parametric instabilities (GPIs), 4 Kerr beam self-cleaning (KBSC), 5 ultra-wide supercontinuum generation (SCG), 6 and intermodal four-wave mixing (IFWM) 7 can be cited among the major recent advances in multimode nonlinear fiber optics.…”
Section: Introductionmentioning
confidence: 99%